Influence of Annealing on Structure and Fatigue Properties of Microalloyed Steel - Rosenberg, Gejza (Communications - Scientific letters of the University of Zilina, 2006)
Advanced microalloyed steels (HSLA steels) contain microstructural components whose mechanical properties can be altered by exposure to elevated temperatures, for example, in application of welding cycles. The objective of this paper is to identify the relative influence of annealing (annealing at 650°C for 25 min) on microstructure and fatigue properties variability of HSLA steels. The results obtained in this work suggest that in spite of no or very small positive effect of annealing on the fatigue limit of HSLA steels with no stress concentrator in its presence it can be expected that the annealing has a negative influence either on fatigue crack initiation or fatigue crack growth.